Three new species of the genus Poeciloderrhis Stål, 1874 from Brazil (Blattodea, Blaberidae, Epilamprinae) and neotype designation for Poeciloderrhis imperialis Rocha e Silva & Jurberg, 1978 - Da Silva, Leonardo De Oliveira Cardoso; Lopes, Sonia Maria (Zootaxa, 2020)
Three new species of Poeciloderrhis are described: P. angelus sp. nov., P. mangaratibensis sp. nov. and P. marombensis sp. nov.. Species delimitation, the tergal modification in the abdomen, the genital plates and their respective structures were analyzed. In addition, a neotype for P. imperialis Rocha e Silva & Jurberg, 1978 is also designated.